Clinicopathological and molecular features of tubo-ovarian carcinosarcomas: a series of 51 cases - Liang, Fan; Shi, Yue; Chen, Yiqing; Tao, Xiang; Ding, Jingxin (Frontiers in Oncology, 2024)
Objective Tubo-ovarian carcinosarcomas are rare, extremely aggressive malignant tumors that contain both carcinomatous and sarcomatous components. Due to the disease’s rarity, developing an effective treatment strategy for ovarian carcinosarcomas has been challenging. A study was conducted to investigate the clinicopathologic and molecular features of this rare disease. Methods We enrolled all patients diagnosed with tubo-ovarian carcinosarcomas from January 2007 to December 2022. The clinical and pathological data were gathered from medical records. Kaplan–Meier curves were plotted to calculate OS and PFS. The Log-rank test and Cox regression model were utilized to explore the relationship between clinicopathological parameters and survival. Patients with cancer tissues available had sequencing with a 242-gene panel done to investigate the mutational landscape and signature of the disease. Results In total, 65% of the patients were diagnosed with advanced-stage cancer. The median PFS and OS of this cohort were 27 and 40 months, respectively, and there was no significant difference in survival between the homologous and heterologous components of sarcoma. Unexpectedly, staging did not have effects on prognosis. All patients had surgical attempts, and suboptimal debulking status was correlated with poorer PFS and OS. MSI was identified in 0% with low Tumor mutation burden (TMB) indicating a poor response to immunotherapy. Low HER2 expression is controversial, according to previous reports, and gives us limited choices with this rare and aggressive disease. We surprisingly found the homologous recombination deficiency (HRD)-positive status was identified in 64% of OCS, which is significantly higher than UCS and other types of epithelial ovarian cancer. The fact that all patients in our cohort who received olaparib as maintenance therapy had survived over 30 months and two had no evidence of recurrence at the latest follow-up might further validate the role of poly (ADP-ribose) polymerase inhibitors (PARPi) in the management of OCS. Conclusion OCS patients seemed to respond to carboplatin/paclitaxel with optimal PFS and OS. Cytoreduction with no residuals proved to be the sole independent prognostic factor. WES should be done to assess the prognosis and assist with the targeted therapy, especially the HRD test, which might help select potential patients who benefit from PARPi.